A Comprehensive Review of Maximum Power Point Tracking (MPPT) Techniques Used in Solar PV Systems - Katche, Musong L.; Makokha, Augustine B.; Zachary, Siagi O.; Adaramola, Muyiwa S. (Energies (Basel), 2023)
Renewable Energy technologies are becoming suitable options for fast and reliable universal electricity access for all. Solar photovoltaic, being one of the RE technologies, produces variable output power (due to variations in solar radiation, cell, and ambient temperatures), and the modules used have low conversion efficiency. Therefore, maximum power point trackers are needed to harvest more power from the sun and to improve the efficiency of photovoltaic systems. This paper reviews the methods used for maximum power point tracking in photovoltaic systems. These methods have been classified into conventional, intelligent, optimization, and hybrid techniques. A comparison has also been made of the different methods based on criteria such as tracking speed, efficiency, cost, stability, and complexity of implementation. From the literature, it is clear that hybrid techniques are highly efficient compared to conventional methods but are more complex in design and more expensive than the conventional methods. This review makes available useful information that can be exploited when choosing or designing MPPT controllers.